2017
DOI: 10.1089/cyber.2016.0759
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Test of How Selfies Change Social Judgments on Facebook

Abstract: Selfies are everywhere on social media. Research has focused only on who is posting selfies and has not addressed the audience members viewing selfies. This study aims to fill this gap by analyzing the judgments people make of selfies posted on Facebook. Using an online experiment, we test how including a selfie on a Facebook status update changes people's appraisals of narcissism, message appropriateness, and social attraction. We also consider how the valence and intimacy of the status update text interplay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…In contrast to Lin et al's study [8] reporting mostly weak correlations below 0.30, the expected associations were in line with the idea that selfitis behavior is directly connected to social media, since individuals can fulfil their social needs, such as self-presentation and the need to belong to. The observed positive associations were also in line with studies demonstrating that selfie-sharing on social media improves one's self-esteem/mood through "likes" [72] and is related to self-presentation behaviors and relationship construction [30,73]. Similarly, and consistent with the authors' expectations, the positive associations between SBS and the number of daily selfies and of friends/followers on social media provided evidence for the criterion-related validity, although correlation values were weak probably due to the lack of any accurate psychometrics measures of the two criteria.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast to Lin et al's study [8] reporting mostly weak correlations below 0.30, the expected associations were in line with the idea that selfitis behavior is directly connected to social media, since individuals can fulfil their social needs, such as self-presentation and the need to belong to. The observed positive associations were also in line with studies demonstrating that selfie-sharing on social media improves one's self-esteem/mood through "likes" [72] and is related to self-presentation behaviors and relationship construction [30,73]. Similarly, and consistent with the authors' expectations, the positive associations between SBS and the number of daily selfies and of friends/followers on social media provided evidence for the criterion-related validity, although correlation values were weak probably due to the lack of any accurate psychometrics measures of the two criteria.…”
Section: Discussionsupporting
confidence: 87%
“…In fact, selfies may help individuals express and fortify their own identity in an online context. According to some scholars ( Nadkarni and Hofmann, 2012 ; Nguyen, 2014 ; Katz and Crocker, 2015 ; Sorokowska et al, 2016 ; Diefenbach and Christoforakos, 2017 ; Etgar and Amichai-Hamburger, 2017 ; Taylor et al, 2017 ; Reich et al, 2018 ), self-presentation, self-promotion, and self-approval are prominent features of selfie experience.…”
Section: Discussionmentioning
confidence: 99%
“…According to Nadkarni and Hofmann (2012) , social media use fulfills two social needs: self-presentation and the need to belong. Selfie-sharing on SNS improves one’s self-esteem/mood through “likes” ( Reich et al, 2018 ), and seems to be especially related to self-presentation behaviors and relationship construction ( Sorokowska et al, 2016 ; Taylor et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon requires further research (Boursier & Manna, 2018b;Bruno et al, 2018;McLean et al, 2019) to more fully understand the possible risks and opportunities related to selfie behavior (e.g., Boursier et al, 2020a;Boursier et al, 2020c;Boursier & Manna, 2018b;Diefenbach & Christoforakos, 2017;McLean et al, 2019). Concerning the opportunities offered by selfie-taking and selfie-sharing, some studies have shown that these activities appear to (i) provide new material for creative works, allowing creators to manage emotions (Bruno et al, 2018;Diefenbach & Christoforakos, 2017), (ii) improve individuals' self-esteem and mood due to "likes" and positive feedback received from others (Reich et al, 2018;Toma, 2013), (iii) enhance selfconfidence and self-attractiveness (Boursier & Manna, 2018b;Grogan et al, 2018), and (iv) contribute to relationship construction (Chua & Chang, 2016;Sorokowska et al, 2016;Taylor et al, 2017). Other studies have found that selfietaking and selfie-sharing represent habitual behaviors that help pass the time, facilitated by needs to belong, document, archive, retain special moments, and be creative (Bij de Vaate et al, 2018;Etgar & Amichai-Hamburger, 2017;Sung et al, 2016).…”
Section: Introductionmentioning
confidence: 99%